Предмет: Математика, автор: grmar7911

Помогите,алгебра 7 класс

Приложения:

Ответы

Автор ответа: alex080297
1

Ответ:

Пошаговое объяснение:

2(2x+1)-3(x-3)-5(3x+1)=4\\

4x+2-3x+9-15x-5=4

-14x+6=4

-14x=-2

x=\frac{1}{7}

\frac{4+3(3x-1)}{2} -1=\frac{2(5+x)}{3}

\frac{4+9x-3}{2} -1=\frac{10+2x}{3}

\frac{1+9x}{2} -1=\frac{10+2x}{3}

\frac{3+27x-6}{6} =\frac{20+4x}{6} \\3+27x-6=20+4x\\23x=20-3+6\\23x=23\\x=1

3.2(2x-5)+1.4(3x+2)=-2.6\\6.4x-16+4.2x+2.8=-2.6\\10.6x=10.6\\x=1

\frac{1-4(2\frac{2}{5}+2.5x) }{5} -\frac{2.2(2x+2.1)}{3} =1

\frac{1-9.6-10x}{5} -\frac{4.4x+4.62}{3} =1

\frac{-8.6-10x}{5} -\frac{4.4x+4.62}{3} =1

\frac{-25.8-30x-22x-23.1}{15} =\frac{15}{15}

-25.8-30x-22x-23.1=15\\-52x=63.9\\x=-\frac{639}{520} =-1\frac{119}{520}

Похожие вопросы